35th Winter School on Vibroacoustical Hazards Suppressions – Wisła, Poland, February 26 – March 02, 2007 - BUKOWSKI, Roman (Archives of Acoustics, 2007)
Traditionally I invite you to acquaint with abstracts of selected lectures submitted to presentation in jubilee 35th Winter School on Vibroacoustical Hazards Suppressions. This national School, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at February/March 2007 in Wisła.The conference is the forum for all environmental vibroacoustics fields. Particularly it concern to traffic noise, industry noise, vibroacoustics of machines, room acoustics, noise protection and similar problems. During the School the theoretical works, experimental, measuring, technical, applied and normative ones are presented.The School lectures, and other conference materials, will be published in the "Materials of the XXXV Winter School on Vibroacoustical Hazards Suppressions" (in Polish) edited by Dr. Mieczysław Roczniak (chairman of the conference). This publication is intend to participants of the School and for many libraries in Poland.Other information about XXXV WS on VHS you can find at address http://ogpta.polsl.pl